Service quality performance of e-hailing services in Sarawak, Malaysia. - Rosli, Anita (University of Tehran, 2025)
With the advancement of communication technology, e-hailing services are becoming more widespread in Malaysia. Even though e-hailing services offer relative advantages compared to other types of public transport, research on the service quality aspects and customer satisfaction is essential to ensure customers receive worthwhile service with the money they spend on the services. Therefore, the growth of the e-hailing sector in Malaysia has drawn attention from the government, service providers, passengers, and even academics to the issues of service quality and customer satisfaction. Much research on service quality has been conducted in Malaysia; however, limited research has yet to be done on e-hailing services specifically for the state of Sarawak (East Malaysia) compared to peninsular areas. Thus, this research aims to measure the service quality performance of e-hailing in Sarawak and investigate the factors influencing passenger satisfaction. Three hundred ninety-two e-hailing users voluntarily participated in the survey, which was conducted in 2023. The partial least squares structural equation modeling (PLS-SEM) was performed to assess the measurement and structural model. The analysis revealed that vehicle condition, customer service, and reliability have a significant one-percent relationship with passenger satisfaction. To ensure e-hailing vehicles are always in good condition, e-hailing companies and government agencies must make it mandatory for e-hailing cars to be maintained periodically. Next, the driver should improve communication skills and show a good attitude to provide excellent customer service. Besides, prompt response to customer orders is a must to ensure e-hailing services are reliable public transportation.